The role of the oblique ligament in the mechanical behavior of the medial collateral ligament of the mongrel dog elbow joint - Some biomechanical aspects - Oliveira, Daniela [UNESP]; Artoni, Silvana Martinez Baraldi [UNESP]; Shimano, Antonio Carlos; Pacheco, Maria Rita [UNESP]; Rossi, Juliana Regina [UNESP]; De Araújo, Marcos Lania [UNESP] (Universidade Estadual de Maringa, 2005)
This study investigated the oblique ligament mechanical contribution to the medial collateral ligament of the canine elbow joint. Fifteen dogs were used for the study of the failure load, displacement, and energy absorption of the medial collateral and oblique ligaments of the canine elbow joint, associate and separately in the joint. Medial collateral ligament failure load and energy absorption were significantly higher in relation to the isolated oblique ligament. When the ligaments were associated in the joint, they presented an increment in failure load, displacement and energy absorption in relation to the ligaments analyzed separately. It was concluded, therefore, that the oblique ligament could have an important paper in the stability of the canine elbow joint, as it favors the medial collateral ligament resistance to the tensile load, one of the main stabilizer of the elbow joint.
Keywords: Biomechanics; Dog; Elbow; Medial collateral ligament; Oblique ligament; collagen type 1; collagen type 3; animal experiment; animal tissue; biomechanics; dog; elbow; energy absorption; joint mobility; joint stability; knee ligament; mechanical stimulation; nonhuman; statistical analysis; tensile strength; viscoelasticity; weight bearing; Animalia; Canis familiaris